PENGEMBANGAN MEDIA PEMBELAJARAN AUGMENTED REALITY SIAR (SIKLUS AIR) UNTUK MENINGKATKAN LITERASI SAINS PESERTA DIDIK - Darma Puteri, Alfianti; Samsul Maarif (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low level of science literacy among students in understanding learning materials. One of them is in understanding the concept of the water cycle which is abstract and the use of inadequate learning media tools. The objectives of this research were: 1) test the feasibility and practicality of Augmented Reality learning media on water cycle material, and 2) determine the effectiveness of Augmented Reality media in improving the science literacy of grade V elementary school students. This research uses an R&D approach with a 4D framework model (define, design, develop, disseminate). The data collection technique of this research is through interviews and questionnaires. This media showed material and media validity levels of 87.5% and 84%, respectively, with a very feasible category. Then, the large-scale trial resulted in an N-Gain score of 70.50%, which shows a very high level of effectiveness, while student responses also reached 84% with a very good assessment category. Based on the results of the study, that Augmented Reality media is feasible to be applied to assist students in learning.